Analisis Kritis Terhadap Matan Hadis Sebagai Upaya Memastikan Otentisitas dan Validitas Hadis - Muhammad Sulaiman; Tajul Arifin; Edy Saputra (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research examines the methodology of critical analysis of hadith matans as an effort to ensure the authenticity and validity of hadiths in the context of Islamic scholarship. The main focus of the research is to identify and analyze critical parameters used in assessing the validity of matan hadith, as well as their implementation in specific case studies. Through a qualitative approach with content and comparative analysis methods, this research reveals that critical analysis of hadith matan requires a comprehensive understanding of the linguistic, historical and doctrinal aspects of Islam. The research results show the importance of integrating multiple criteria in the hadith matan verification process to ensure the validity and applicability of the hadith in the contemporary context.